KAJIAN PEMASANGAN GIRDER JEMBATAN TOL PORONG – GEMPOL TERHADAP PENYIMPANGAN NILAI REAKSI DAN JARAK ANTAR GIRDER SESUAI BROSUR PT.WIKA - Winoto, Ery Prasetyo Hadi; Priyono, Pujo; K, Totok Dwi (Universitas Muhammadiyah Jember, 2019)
The existence of toll roads cannot be separated from the emergence of a need so that road public facility providers have become economically valuable. The prestressed girders built on the Porong - Gempol toll bridge are in fact quite effective because in addition to concrete it can bear a bigger load than before and can reduce its own weight and cross-sectional size. In the next case, the girder of the Porong-Gempol Toll Road is greater than CTC which is contained in the brochure of the company itself